Effective School Discipline Practices of Some Primary Schools in Pema Gatshel Dzongkhag - Norbu, Tshering (International Journal of Humanities and Education Development (IJHED), 2021)
The study was conducted under Pema Gatshel Dzongkhag (district) to investigate the effectiveness of school discipline under Pema Gatshel district in Bhutan. The main objective of this article was to evaluate the perception of the effective school discipline according to the principals, teachers, and parents. This paper was a qualitative study based on in-depth semi-structured interviews which were limited to forty-five key participants from six different schools under the Pema Gatshel district. Data were analyzed employing content analysis. The major findings of this study revealed that for efficient functioning of school discipline policy in schools, various stakeholders like parents, teachers, students and the community should work collaboratively. The study also revealed that schools should include students and parents in the decision-making process particularly while trying to bring changes to school discipline policy.